Inspired by this question (and far more straightforward, I am guessing), Mathematica tells us that $$\sum_{k=1}^{\infty}\dfrac{{\sin(k)}}{k}$$ converges to $\dfrac{\pi-1}{2}$.

Presumably, this can be derived from the similarity of the Leibniz expansion of $\pi$ $$4\sum_{k=1}^{\infty}\dfrac{(-1)^{k+1}}{2k-1}$$to the expansion of $\sin(x)$ as $$\sum_{k=0}^{\infty}\dfrac{(-1)^k}{(2k+1)!}x^{2k+1},$$ but I can't see how...

Could someone please explain how $\dfrac{\pi-1}{2}$ is arrived at?

  • $\begingroup$ Well, $\sin(k)/k$ converges to $0$ at the same rate that $1/k$ converges to $0$, in that $\sin(k)$ can be arbitrarily close to $1$ so it can't be "faster" than that. $\endgroup$ – Thomas Andrews Jun 10 '14 at 17:47
  • $\begingroup$ Please excuse my stupidity! ... Question now updated. $\endgroup$ – martin Jun 10 '14 at 17:55
  • 1
    $\begingroup$ Fourier series. $\endgroup$ – Pedro Tamaroff Jun 10 '14 at 18:06
  • $\begingroup$ Wow - thanks for all of the answers (I will look carefully before upvoting!) - Quickest responses to any question I have asked so far! :) $\endgroup$ – martin Jun 10 '14 at 18:11

Here is one way, but it does not use the series you mention so much. I hope that's OK.

The series is:

$$\sin(1)+\frac{\sin(2)}{2}+\frac{\sin(3)}{3}+\cdot\cdot\cdot $$

$$\Im\left[e^{i}+\frac{e^{2i}}{2}+\frac{e^{3i}}{3}+\cdot\cdot\cdot \right]$$

Let $\displaystyle x=e^{i}$.

$$\Im\left[x+\frac{x^2}{2}+\frac{x^3}{3}+\cdot\cdot\cdot \right]$$


$$\Im \left[1+x+x^{2}+x^{3}+\cdot\cdot\cdot \right]$$

This is a geometric series, $\displaystyle \frac{1}{1-x}$

$$\Im [\frac{1}{1-x}]$$


$$-\Im[\ln(x-1)]=-\Im [\ln(e^{i}-1)]$$

Now, suppose $$\ln(e^{i}-1)=a+bi$$,



Equate real and imaginary parts:

$$\cos(1)-1=e^{a}\cos(b)\\ \sin(1)=e^{a}\sin(b)$$

divide both:




But we need the negative of this, so finally:


  • 3
    $\begingroup$ It is worth remarking that $1 + x + x^2 + \cdots$ diverges because $|e^i| = 1$. $\endgroup$ – glebovg Jun 28 '14 at 4:52
  • $\begingroup$ @glebovg Then how can you still write the sum as 1/(1-x) if the series diverges? $\endgroup$ – Vasting May 15 '16 at 18:47
  • 1
    $\begingroup$ @Vasting: You can't, but it's not actually necessary for the proof. The series $z + \frac{1}{2} z^2 + \frac{1}{3} z^3 + \dots$ is the series for $-\ln(1 - z)$, and it converges everywhere on the unit circle except at $z = 1$. So it's not necessary to differentiate and then integrate as this answer does. $\endgroup$ – Michael Seifert Jan 26 '18 at 20:24

As a generalization, if $a$ is not an integer,

$$ \sum_{k=-\infty}^{\infty} \frac{\sin k}{k+a} = \pi \Big(\cos (a) -\sin (a) \cot (\pi a) \Big).$$

This result can be derived using contour integration.

Using the kernel function $\pi \cot(\pi z)$ won't work in the sense that $$\int_{|z|=N+\frac{1}{2}} \frac{\pi \cot(\pi z) e^{iz}}{z+a} \, dz$$ won't vanish as $N \to \infty$ through the positive integers.

So instead we will use the kernel $\pi e^{-i \pi z} \csc(\pi z)$, which also has simple poles at the integers with residue $1$.

To see that the integral vanishes, notice that as $\text{Im}(z) \to + \infty$, $\left|e^{-i \pi z} \csc(\pi z) e^{iz} \right|$ decays like $2 e^{-\text{Im}(z)}$. And as $\text{Im}(z) \to - \infty$, $\left|e^{-i \pi z} \csc(\pi z) e^{iz} \right|$ decays like $2 e^{(2 \pi -1) \, \text{Im}(z)}$.

So summing the residues, we get

$$2 \pi i \sum_{k=-\infty}^{\infty} \text{Res} \left[\frac{\pi e^{- i \pi z} \csc(\pi z)e^{iz}}{z+a}, k \right] + 2 \pi i \ \text{Res} \left[\frac{\pi e^{-i \pi z} \csc(\pi z)e^{iz}}{z+a},-a \right] = 0,$$

which implies

$$ \begin{align} \sum_{k=-\infty}^{\infty}\frac{e^{ik}}{k+a} &= - \text{Res} \left[\frac{\pi e^{-i \pi z}\csc(\pi z) e^{iz}}{z+a},-a \right] \\ &= - \lim_{z \to -a} \pi e^{-i \pi z} \csc (\pi z) e^{iz} \\ &= \pi e^{i \pi a} \csc(\pi a)e^{-ia} \\ &= \pi \Big(\cos (\pi a) + i \sin (\pi a) \Big) \csc (\pi a)\Big( \cos (a) - i \sin (a)\Big) \\ &= \pi \ \frac{\cos ( a) \cos (\pi a) + \sin (a) \sin (\pi a)}{\sin (\pi a)} + i \pi \ \frac{\cos(a) \sin (\pi a) - \sin(a) \cos (\pi a)}{\sin (\pi a)}. \end{align} $$

Then equating the imaginary parts on both sides of the equation, we get

$$ \sum_{k=-\infty}^{\infty} \frac{\sin k}{k+a} = \pi \Big(\cos (a) - \sin (a) \cot (\pi a) \Big).$$

Notice that nothing changes if we remove $k=0$ from the summation.

So if we let $a \to 0$ on both sides of the equation, we get

$$2 \sum_{k=1}^{\infty} \frac{\sin k}{k} = \pi - 1.$$


$$\sum_{n=1}^{+\infty}\frac{\sin n}{n}=\Im\sum_{n=1}^{+\infty}\frac{e^{in}}{n}=\Im\left(-\log(1-e^i)\right)=\pi-\arg(e^i-1)=\frac{\pi-1}{2}.$$


$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ \begin{align} \sum_{k = 1}^{\infty}{\sin\pars{k} \over k}&= -1 + \sum_{k = 0}^{\infty}{\sin\pars{k} \over k} \end{align}

With Abel-Plana Formula: \begin{align} \sum_{k = 1}^{\infty}{\sin\pars{k} \over k}&= \color{#c00000}{\Large -1} +\ \overbrace{\int_{0}^{\infty}{\sin\pars{x} \over x}\,\dd x} ^{\ds{=\ \color{#c00000}{\Large{\pi \over 2}}}}\ +\ \color{#c00000}{\Large\half}\ \overbrace{\lim_{x \to 0}{\sin\pars{x} \over x}}^{\ds{=\ 1}} \\[3mm]&\phantom{=}+ \ic\ \underbrace{\int_{0}^{\infty}\bracks{% {\sin\pars{\ic x} \over \ic x} - {\sin\pars{-\ic x} \over -\ic x}} {\dd x \over \expo{2\pi x} - 1}}_{\ds{=\ 0}} \end{align}

$$\color{#66f}{\large% \sum_{k = 1}^{\infty}{\sin\pars{k} \over k} = {\pi - 1 \over 2}} $$


It follows from the formula $-log(1-z)=\sum_{j=1}^\infty \frac{z^j}{j}$ for $|z|\leq 1$ and $z\neq 1$. Then letting $z_0=e^{i}=\cos 1 + i\sin 1$. Then the sum you want is the imaginary part of $-\log(1-z_0)$.

Since the imaginary part of $\log$ is the angle, then your sum is $$\arctan\left(\frac{\sin 1}{1-\cos 1}\right)=\arctan\left(\cot\frac12\right) =\frac{\pi}{2}-\frac{1}{2}$$

  • $\begingroup$ Thanks for the $\arg$ explanation - it all follows quite nicely now :) $\endgroup$ – martin Jun 10 '14 at 18:34

Using the power series $$ -\log(1-z)=\sum_{k=1}^\infty\frac{z^k}{k} $$ we get $$ \begin{align} \sum_{k=1}^\infty\frac{\sin(k)}{k} &=\frac1{2i}\sum_{k=1}^\infty\frac{e^{ik}-e^{-ik}}{k}\\ &=\frac1{2i}\left[-\log(1-e^i)+\log(1-e^{-i})\right]\\ &=\frac1{2i}\log(-e^{-i})\\ &=\frac{\pi-1}{2} \end{align} $$ That is, since $1-e^{-i}$ is in the first quadrant and $1-e^i$ is in the fourth, the imaginary part of $-\log(1-e^i)+\log(1-e^{-i})$ is between $0$ and $\pi$.


You have a function $f:[0,2\pi]\to\Bbb R$ given by $x\mapsto \dfrac{\pi-x}2$ which you can extend periodically to get an odd function $f:\Bbb R\to\Bbb R$. Since $f$ is odd, the even Fourier coefficients vanish, and the odd coefficients of $f$ are given by $$\frac{1}{\pi}\int_0^{2\pi}\sin kx\frac{ \pi-x}2dx=-\frac 1 {2\pi}\int_0^{2\pi}x \sin kxdx$$

Integrating by parts gives $$\int_0^{2\pi}x \sin kxdx=-\frac{2\pi}{k}$$ so that the coefficients are $\dfrac 1 k$, i.e. we have the Fourier expansion $$ \sum_{k=1}^{\infty}\frac{\sin kx}k$$

Since $f$ is differentiable at $x=1$ we can plug in $x=1$ to get $$\frac{\pi-1}2=\sum_{k=1}^{\infty }\frac{\sin k}k$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.